Pengaruh Tarif Pajak dan Sosialisasi Perpajakan Terhadap Kepatuhan Pajak Pelaku UMKM Setelah Penerapan PP No.23 Tahun 2018: Prespektif Sunset Clause - Qurratul Aini; Fauzan Misra; Riyadi Aprayuda (Jurnal Akuntansi dan Governance Andalas, 2020)
This study aims to empirically examine the effect of reducing tax rates and taxation socialization on taxpayer compliance with MSMEs after the application of PP No. 23 of 2018 from the perspective of the sunset clause. The Sunset clause is The sampling technique that uses purposive sampling. Based on the criteria set, the number of samples obtained was 60 respondents. The results of this study indicate that the reduction in tax rates has a significant influence on taxpayer compliance. Likewise, tax socialization also has a significant effect on tax compliance. As a practical contribution, the results of this study imply that the tax authorities are expected to be able to make policies that are perceived as fair and do not burden taxpayers regarding tax rates or other rules. In addition, the tax authorities need to make taxation socialization an important tool to improve tax compliance.